Design and synthesis of active vitamin D analogs - Eduardo, Silvina Laura (2010)
A review of the design and synthesis of structural analogs of the vitamin D hormone recently investigated in our laboratories, and the first report on a new class of vitamin D analogs characterized by an aromatic D-ring, is described.